Contemporary theatre Samuel Beckett : Waiting for Godot - Schneider, Alan; Kuney, Jack; Worthington, Miner (History of the drama / produced by Harold Mantell, 1976)
A play that epitomizes both the modern condition and contemporary theatre. Presents Act II in its entirely, beginning with the return of Didi and Gogo to what they were doing in Act I - Waiting for Godot